Highly Selective Au/ZnO via Colloidal Deposition for CO2 Hydrogenation to Methanol: Evidence of AuZn Role - Hasliza Bahruji; Mshaal Almalki; Norli Abdullah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Gold, Au nanoparticles were deposited on ZnO, Al2O3, and Ga2O3 via colloidal method in order to investigate the role of support for CO2 hydrogenation to methanol. Au/ZnO was also produced using impregnation method to investigate the effect of colloidal method to improve methanol selectivity. Au/ZnO produced via sol immobilization showed high selectivity towards methanol meanwhile impregnation method produced Au/ZnO catalyst with high selectivity towards CO. The CO2 conversion was also influenced by the amount of Au weight loading. Au nanoparticles with average diameter of 3.5 nm exhibited 4% of CO2 conversion with 72% of methanol selectivity at 250 °C and 20 bar. The formation of AuZn alloy was identified as active sites for selective CO2 hydrogenation to methanol. Segregation of Zn from ZnO to form AuZn alloy increased the number of surface oxygen vacancy for CO2 adsorption to form formate intermediates. The formate was stabilized on AuZn alloy for further hydrogenation to form methanol. The use of Al2O3 and Ga2O3 inhibited the formation of Au alloy, and therefore reduced methanol production. Au/Al2O3 showed 77% selectivity to methane, meanwhile Au/Ga2O3 produced 100% selectivity towards CO. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).